AUDIO TO SIGN LANGUAGE CONVERTER - AMAN MAURYA; JASMEET KAUR; RIYA GARG; SUDEEP VARSHNEY (International Journal of Multidisciplinary Research and Studies, 2022)
There is a communication gap between people who are not able to understand the thoughts of those people having this problem so with the help of AI this application artificially which will be able to help those people having no sense of understanding the thoughts of others by their movement or motion. We will add some signs of the English alphabet as predefined expressions. This application we made is for deaf people having hearing problems with them.